Extensive Mitochondrial Heteroplasmy in Natural Populations of a Resurging Human Pest, the Bed Bug (Hemiptera: Cimicidae) - Robison, G A; Balvin, O; Schal, C; Vargo, E L; Booth, W (Journal of medical entomology, 2015)
Homoplasmy, the occurrence of a single mitochondrial DNA haplotype within an individual, has been the accepted condition across most organisms in the animal kingdom. In recent years, a number of exceptions to this rule have been reported, largely due to the ease with which single nucleotide polymorphisms can be detected. Evidence of heteroplasmy-two or more mitochondrial variants within a single individual-has now been documented in a number of invertebrates; however, when present, heteroplasmy usually occurs at low frequencies both within individuals and within populations. The implications of heteroplasmy may be far reaching, both to the individual in relation to its health and fitness, and when considering the evolutionary dynamics of populations. We present novel evidence for frequent mtDNA heteroplasmy in the bed bug, Cimex lectularius L. (Hemiptera: Cimicidae). Our findings show that heteroplasmy is common, with 5 of 29 (17%) populations screened exhibiting two mitochondrial variants in a ∼1:2 ratio within each individual. We hypothesize that the mechanism underlying heteroplasmy in bed bugs is paternal leakage because some haplotypes were shared among unrelated populations and no evidence for nuclear mitochondrial DNA sequences was detected.
Keywords: Ectoparasitic Infestations; cytochrome oxidase I; štěnice; haplotypy; Humans; Missouri; mitochondriální DNA; Cimicidae; DNA, Mitochondrial; Female; Haplotypes; lidé; zvířata; Cimex lectularius; Hemiptera; paternal leakage; infestace ektoparazity; ženské pohlaví; Male; Oklahoma; Animals; mužské pohlaví; Bedbugs